Peran Media Sosial Instagram (@dinkesbanjarmasinnews) Sebagai Sarana Komunikasi dan Promosi Kesehatan oleh Dinas Kesehatan Kota Banjarmasin: Penelitian - Syafaruddin; M.Agus Humaidi; Junaidy (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Banjarmasin City Health Office must comply with applicable regulations and ethics in the use of social media for health promotion purposes. This includes compliance with regulations governing health advertising, information that may be shared, and ways of interacting with the public. Disseminating information that violates regulations or that appears to promote certain products or services without a strong scientific basis can damage the Health Office's credibility and undermine public trust in the information provided. This demonstrates the Health Office's Instagram account's role in encouraging the public to change behavior towards a healthier lifestyle.